(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Plant extracts have been used as therapeutic agents and have become important for human health worldwide for a long time. The present study aimed to investigate and compare the effect of Adiantum capillus, and Prosopis farcta plant extracts on an in-vitro wound healing. Methods: Ethanol extracts of both plants have been prepared and used in the present investigation to study the immunomodulatory role of human peripheral blood mononuclear cells (PBMC). Total phenolic content (TPC) of both extracts was measured by using the aluminum chloride colorimetric method. In vitro antioxidant actives were determined by the DPPH, ABTS, and FRAP free radical scavenging activities were also measured. Results: Both extracts of Prosopis farcta and Adiantum capillus showed abilities to scavenge DPPH and ABTS free radicals. The Results were showed that the A. capillus extracts had higher antioxidant potential and polyphenol contents than P. farcta extracts. Conclusion: The whole plant extract of Adiantum capillus-veneris is capable for free radical scavenging molecules and it can be used as a potential source of natural antioxidants for wound healing treatments.